Análisis de crecimiento de canavalia en zona plana del Valle del Cauca - Cortés R. Harry; Mejía Sara; Ortiz G. Sanín; Reyes Paula A.; Ortiz José J (Acta Agronómica)
El análisis se realizó en condiciones de campo, en dos localidades (Candelaria y Palmira), determinando los componentes de rendimiento (kg), altura (cm) y fenología (dds/floración). Se empleó un diseño completamente al azar con cinco repeticiones. El crecimiento de C. ensiformis no mostró diferencias entre las localidades evaluadas. El desempeño fisiológico en la acumulación de fotosintatos se concentró en mayor proporción en el órgano vertedero â€œfrutoâ€?, que representa entre el 60 y 75% de MS total. La dinámica de acumulación de MS mostró correlación en los índices medidos (TCC, TCR, TAN, IAF).

Abstract

Analysis of growth of canavalia in the plane zone of Valle del Cauca. Under conditions of field, in two localities (Candelaria and palmira), determining the components of yield (Kg), height (cm) and fenology (d/flower). A design at random with five (5) repetitions was used completely. The growth of Canavalia ensiformis does not show differences enters the evaluated localities. The physiological performance in the accumulation of photosintates is it accumulated in greater proportion in the organ garbage dump â€œfruitâ€?, that represents between 60 and 75% of dry matter. The dynamics of accumulation of MS shows correlation in the measured indices (NAR, LAI, RGR).

Key words: Canavalia ensiformis, biological analysis, phenology, yield components.